Pengalaman Guru PAI dalam Menghadapi Tantangan Multikultural di Sekolah MA Al Wardah Tembung - Raihan Albani Dalimunthe; Sokon Saragih; Muslem (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to describe the experiences of Islamic Religious Education (PAI) teachers in facing multicultural challenges at MA Al Wardah Tembung. Using a qualitative phenomenological approach, data were collected through interviews, observations, and documentation. The results show that PAI teachers successfully manage student diversity through empathetic, inclusive, and contextual approaches. They instill the values of tolerance, brotherhood, and religious moderation, creating a harmonious learning atmosphere. Diversity in the school becomes a potential strength that enriches the learning process and shapes students’ open-minded and respectful character.